Deep multilayer brain proteomics identifies molecular networks and Netrin‐1 accumulation in Alzheimer's disease progression: Genetics/omics and systems biology. (7th December 2020) - Bai, Bing; Wang, Xusheng; Li, Yuxin; Chen, Ping‐Chung; Yarbro, Jay M.; Beach, Thomas G.; Peng, Junmin
Abstract: Background: Alzheimer's disease (AD) displays a long asymptomatic stage prior to development of dementia. Identification of molecular alterations during AD progression would provide insight into temporal alterations associated with AD. Method: AD stage‐associated molecular networks were characterized by mass spectrometry in 90 frontal cortical tissue samples in five groups, including controls with low/high amyloid plaque and tau tangle pathology (LPC and HPC, respectively), cases with high Aβ pathology and slight mild cognitive impairment (MCI), late‐stage AD with high plaque/tangle pathology, and samples with progressive supranuclear palsy (PSP). We additionally performed whole proteome comparisons between human AD and the 5XFAD and Tau P301S mouse models. Protein targets implicated as altered by AD progression in the proteomic analyses were validated by affinity assays and immunostaining in human tissue and mouse models. Results: AD stage‐associated molecular networks were characterized by profiling 14, 513 proteins and 34, 173 phosphosites in human brain with mass spectrometry, highlighting 173 protein alterations in 17 pathways. In total 16, 128 proteins in 5xFAD and wild‐type mouse cortex were profiled, and share 97, 89, and 169 protein alterations with HPC, MCI, and AD, respectively, whereas Tau P301S mice share less than 15 protein alterations with each group. Neither mouse model shares more than 15 non‐tau phosphopeptide alterations with each AD sub‐group, although Tau P301S shares up to 78 phospho‐Tau peptides with human AD. During validation of proteins implicated in the proteome characterization, Netrin‐1 levels were found to increase in AD stage progression by immunoblotting but was not augmented in any other neurodegenerative disease cases tested. Additionally, affinity assays demonstrated a direct Aβ‐Netrin‐1 interaction, and immunostaining demonstrated Netrin‐1 and amyloid plaque colocalization in human AD and 5X‐FAD brain tissues, but not in Tau P301S. Conclusion: Our proteomic analyses reveal altered proteins in AD and related mouse models. Human‐mouse comparisons suggest 5xFAD mice resemble symptomatic AD and that Tau P301S mice reproduce only AD‐related Tau phosphorylation. Netrin‐1 accumulates in AD, shows direct Aβ binding, and colocalizes with amyloid plaques in human AD and mouse 5XFAD brain tissue, and may be vital to AD pathogenesis. These results provide novel insights into AD‐associated proteins and pathways.